Creating a Culture of Success: Fine-Tuning the Heart and Soul of Your Organization - Charles B Dygert (Prentice Hall of India private limited, 2008)
Culture constitutes shared values of the individuals within, and it is the corporate heart and soul of an organization. Without the right culture, the organization slows down, loses its vitality, and could go into a type of cardiac arrest. The authors, in this book, define what organizational culture is and how the success of the culture drives the success of the enterprise. Their concepts are driven home with real-world examples drawn from their experience with a wide variety of organizations. The authors then provide simple, straightforward steps to building a culture of success, along with tools to assist in understanding the common barriers to an effective culture.